Peran Pembiayaan Murabahah Terhadap Perkembangan Usaha dan Kesejahteraan Pelaku UMKM Pasar Tradisional - Camelia, Dina; Ajib Ridlwan, Ahmad (Universitas Negeri Surabaya, 2018)
Micro, Small and Medium Enterprises or MSMEsis economic activities that contribute to the development and economic growth of Indonesia. However, MSMEs have limitations such as capital due to access to financial institutions such as bank.Financial institutions that can overcome these problems are islamic microfinance institutions such as Baitul Maal Wat Tamwil (BMT) with murabahah financing. This study uses a qualitative research method wich aims to determine the role of murabahah financing towards business development and welfare of micro and small businessman in the traditional Ketapang-Sampang market. Based on the results of research conducted at BMT UGT Sidogiri, Ketapang-Sampang Branch, it can be concluded that murabahah financing was used in the business development and wefare of the members who received